Strategi bank syariah dalam mendukung ekonomi umat: solusi keuangan berbasis syariah - Syakuro, Muhammad Kifah Abdan (Maliki Interdisciplinary Journal, 2025)
This article discusses the strategies implemented by Islamic banks in supporting the economic growth of the people through financial solutions based on Islamic principles. In this context, Islamic banks play an important role as financial institutions that offer financial products and services in accordance with Islamic law, such as profit sharing (mudharabah), partnership (musyarakah), and usury-free financing. The goal is to provide fair, inclusive, and sustainable solutions for the community, especially for the small and medium enterprise (SME) sector and individuals who have not been reached by conventional banking services. This study reviews the strategic approach of Islamic banks in expanding financial access, increasing Islamic financial literacy, and encouraging financial inclusion by maintaining the principles of justice, transparency, and partnership. In addition, it also discusses the challenges faced by Islamic banks in facing global competition and adapting to developments in financial technology (fintech). Through the implementation of these strategies, Islamic banks are expected to contribute significantly to strengthening the people's economy and achieving wider community welfare.